MORPHOLOGICAL AND MOLECULAR IDENTIFICATION OF AN EDIBLE RUSSULA MUSHROOM IN NORTHEAST VIETNAM - Nhu Anh, Chung; Minh Chi, Nguyen; Tam Kiet, Trinh; Duy Long, Pham; Thi Thu Thuy, Pham; Van Loi, Vu; Dell, Bernard (Journal of Forestry Science and Technology, 2023)
Wild mushrooms are extensively gathered by rural communities throughout the uplands of northern Vietnam and nearby countries for food and medicine. These non-wood forest products are important for the livelihood of numerous rural communities. Many of these fungi form symbiotic relationships with the roots of certain species of forest trees, and the fruiting bodies can not be produced in artificial media. In the northeast region of the country, an edible red Russula (Nấm chẹo or Nấm hồng cô) has been harvested from under wild Castanopsis, Engelhardia and Lithocarpus trees by local people for a long time. However, the identity of this Russula is unknown. We collected basidiomes of this edible Russula in Cao Bang, Bac Giang and Quang Ninh provinces and described its morphological features. We used ITS rDNA and LSU rDNA sequence analysis to compare with other similar taxa in GenBank. Morphological and molecular analysis identified the taxon as Russula griseocarnosa, previously described from southern Yunnan, China. There is strong interest by local governments to commercialize R. griseocarnosa in Vietnam. However, over-harvesting could have detrimental effects on the population of this edible species. Therefore, further studies are needed to quantify the ecological requirements and to develop sustainable harvesting protocols of this edible species in Vietnam.